Proceedings of the 17 Th International Symposium on Management (INSYMA 2020) 2020
DOI: 10.2991/aebmr.k.200127.060
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Consumer-Based Brand Equity on Customer Satisfaction and Brand Loyalty in the Coffee Bean & Tea Leaf or Maxx Coffee

Abstract: The purpose of this study is to examine whether consumer-based brand equity (physical quality, staff behavior, self-compatibility, brand identification, and lifestyle congruence) of Coffee Bean & Tea Leaf Surabaya or Maxx Coffee Surabaya have a positive impact on customer satisfaction. This study examined 150 Coffee Bean & Tea Leaf customers and 150 Maxx Coffee customers in Surabaya who had bought the coffee. Structural equation modeling was used to analyze the constructs and overall model. The results of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 11 publications
2
6
0
3
Order By: Relevance
“…Customer satisfaction can affect brand loyalty. 25 Research of Soleh et al (2021), shows customer Satisfaction can influence on brand loyalty positively 26 Research of Javed et al (2021), the findings of this study also validate that customer satisfaction has a significant effect on brand loyalty. 27 Research results of Lee ( 2019), found customer satisfaction can positive significant influence on brand loyalty.…”
Section: Customer Satisfactionsupporting
confidence: 68%
See 1 more Smart Citation
“…Customer satisfaction can affect brand loyalty. 25 Research of Soleh et al (2021), shows customer Satisfaction can influence on brand loyalty positively 26 Research of Javed et al (2021), the findings of this study also validate that customer satisfaction has a significant effect on brand loyalty. 27 Research results of Lee ( 2019), found customer satisfaction can positive significant influence on brand loyalty.…”
Section: Customer Satisfactionsupporting
confidence: 68%
“…12 Research of , obtained the results that influence variable brand identification on customer satisfaction is nothing. 13 Based on previously research above. The hypothesis: H2 : Brand identification has no signification effect on customer satisfaction.…”
Section: Brand Indentificationmentioning
confidence: 99%
“…Oliver (1981, p. 25) defined CS as “the summary psychological state resulting when the emotion surrounding disconfirmed expectations is coupled with the consumer’s prior feelings about the consumption experience.” Additionally, Fornell (1992) stipulated that when customers buy goods or services, they tend to shape their attitudes based on that experience. The literature has stressed a number of factors that lead to CL, of which CS is a key one (Saleem et al , 2017; Leninkumar, 2017; Rambocas et al , 2018; Omoregie et al , 2019; Hoang, 2019; Ledikwe et al , 2019; Indarini and Margaretha, 2020; Kataria and Saini, 2020). CL was defined by Lam et al (2004, p. 307) as the repeated preference and support to a certain service provider: “Satisfied customers appear to be willing to repeat patronizing the service provider and also to recommend the provider to other customers”.…”
Section: Model and Hypotheses Developmentmentioning
confidence: 99%
“…Kataria and Saini (2020) concluded that CS has a positive and substantial effect on BL for oral care products in India, with full CS mediation between lifestyle congruence and brand trust to BL. Recently, Saputra and Margaretha (2020) investigated the influence of CBBE elements on CS and CL. They found that lifestyle, ideal self-congruence, physical quality and staff behavior significantly affect CS.…”
Section: Airline Brand Equitymentioning
confidence: 99%
See 1 more Smart Citation